2022
DOI: 10.1111/caim.12510
|View full text |Cite
|
Sign up to set email alerts
|

A predictive structural model of new ways of working on innovative work behaviour: Higher education perspective in the Gulf Cooperation Council

Abstract: This study examined the relationship between compulsory new ways of working (flexible work design, workplace design at home, advanced information and communication technology [ICT]‐based communications and culture of innovation) and faculty members' innovative work behaviour. The mediating role of work–life balance and employees' satisfaction with new ways of working in the relationship between new ways of working and innovative work behaviour was also examined. Building on established measurement scales, a qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 76 publications
1
9
0
Order By: Relevance
“…Recent research on the antecedents of innovative work behavior abounds, and has focused on a wide range of determinants such as cognitive processes (Kmieciak, 2021), psychological processes including self-efficacy (Bak et al, 2022;Nilasari et al, 2022) and psychological thriving (Kim and Beehr, 2022), interpersonal processes of knowledge sharing (Abualoush et al, 2022) and organizational practices such as job design (Almahamid and Ayoub, 2022) and support for creativity (El-Kassar et al, 2022). Because the research domain of innovative work behavior is extensive, we limit the scope of this research to the interaction of intrinsic and extrinsic motivating factors of innovative work behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research on the antecedents of innovative work behavior abounds, and has focused on a wide range of determinants such as cognitive processes (Kmieciak, 2021), psychological processes including self-efficacy (Bak et al, 2022;Nilasari et al, 2022) and psychological thriving (Kim and Beehr, 2022), interpersonal processes of knowledge sharing (Abualoush et al, 2022) and organizational practices such as job design (Almahamid and Ayoub, 2022) and support for creativity (El-Kassar et al, 2022). Because the research domain of innovative work behavior is extensive, we limit the scope of this research to the interaction of intrinsic and extrinsic motivating factors of innovative work behavior.…”
Section: Introductionmentioning
confidence: 99%
“…, 2022) and psychological thriving (Kim and Beehr, 2022), interpersonal processes of knowledge sharing (Abualoush et al. , 2022) and organizational practices such as job design (Almahamid and Ayoub, 2022) and support for creativity (El-Kassar et al. , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…de Gennaro, 2019;Demerouti et al, 2015), show that such autonomy from the employer to alter complexity and effort of tasks, leads the employees to believe that the organization is likely to consider them for more responsible and senior roles, thus paving a path to a better future for them. Allowing employees to seek challenges has been shown to have a positive effect on constructs that somewhat resemble ERB, such as organizational citizenship behaviour (Andrade and Neves, 2022), and innovative work behaviour (Almahamid and Ayoub, 2022). Therefore, this component of job crafting influences ERB both directly and also partially through workplace flourishing.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, factors such as job satisfaction and perceived work-life balance reported by employees have led to innovative work behaviour and ERB assessed by their supervisors (Almahamid and Ayoub, 2022). Therefore, it is posited that workplace flourishing will have similar influence on ERB of NFEs that work in family firms.…”
Section: Workplace Flourishing and Extra-role Behaviourmentioning
confidence: 99%
“…As prior studies exhibited that the number of GCC outbound students is substantial, repatriated students and their adjustment challenges, particularly in the work environment, should be examined and improved. Nevertheless, research on the labor market in the GCC (Bokhari 2020;Almahamid and Ayoub 2022;Al-Asfour et al 2022) revealed that outbound students from the GCC prefer and continue to pursue degrees that do not correlate with their labor market demands, making research on repatriates' adjustment to work environment a realistic option.…”
Section: Introductionmentioning
confidence: 99%